Teoría de las situaciones didácticas - Chavarría, Jesennia (2008)
The main aspects of the concept of Didactical Situation by G. Brousseau are described. Specifically, the relationship between Didactical Situation and Non Didactical Situation; some “effects” within the Didactical Situations and the different types of them are considered.